TrackE (Tracking Device) / Nuralia Natasha Abdul Halim … [et al.] - Abdul Halim, Nuralia Natasha; Mohd Razi, Muhammad Akmal Danial; Mashor, Yasmin Dudayeva; Rodzli, Shafiqah Aliya; Kamarudin, Muhammad Hafeez Iqmal; Daud, Mohammad Farez; Azis, Siti Noraziana (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
People tend to forget where they placed their belongings and end up purchasing new ones just because they cannot find them. TrackE is a sticker looking small device which shows its location on TrackE app. It can be used to frequently missing belongings such as remote, keys and wallet. Adults who required assistance locating their valuables were the target group for TrackE. It also can be used to vehicle and pets. When a robbery occurs, TrackE can assists them in immediately contacting the authorities. We aspire to provide a better and safer way of life for our users. To be different with other electronic industry, we developed a worldwide ecosystem that allows consumers to effortlessly connect their devices while also ensuring that they engage safely with our application and other devices.